2013
DOI: 10.1371/journal.pone.0075346
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Host Transcriptome from Demyelinating Spinal Cord of Murine Coronavirus-Infected Mice

Abstract: Persistent infection of the mouse central nervous system (CNS) with mouse hepatitis virus (MHV) induces a demyelinating disease pathologically similar to multiple sclerosis and is therefore used as a model system. There is little information regarding the host factors that correlate with and contribute to MHV-induced demyelination. Here, we detail the genes and pathways associated with MHV-induced demyelinating disease in the spinal cord. High-throughput sequencing of the host transcriptome revealed that demye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 144 publications
3
21
0
Order By: Relevance
“…Four week old C57BL/6 mice were inoculated intracranially with DM (RSA59) or NDM (RSMHV2) strains using the LD 50 as described in prior studies [10][11][12]. To confirm infection, histopathology and immunohistochemistry were performed on liver, brain and spinal cord sections from mice whose spinal cords were processed for Microarray analysis.…”
Section: Acute and Chronic Pathology Of Mice Infected With Dm And Ndmmentioning
confidence: 99%
See 1 more Smart Citation
“…Four week old C57BL/6 mice were inoculated intracranially with DM (RSA59) or NDM (RSMHV2) strains using the LD 50 as described in prior studies [10][11][12]. To confirm infection, histopathology and immunohistochemistry were performed on liver, brain and spinal cord sections from mice whose spinal cords were processed for Microarray analysis.…”
Section: Acute and Chronic Pathology Of Mice Infected With Dm And Ndmmentioning
confidence: 99%
“…Our recent studies using Affymetrix microarray analysis revealed that RSA59 induces IFN-gamma inducible genes and innate immune-activating pathway genes during the acute stage of infection [9]. Recent studies using a high-throughput RNA-Seq approach also revealed expression of several genes involved in macrophage function, immune infiltration, and changes in cytokine expression levels in response to persistent MHV infection in mice [10].…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, it was reported that microglial necroptosis in circumstances of lysophosphatidylcholine demyelination leads to repopulation by pro-regenerative CD11c+ microglia, as blocking of this mechanism prevented remyelination (148). Of note, demyelination induced by mouse hepatitis virus also led to enrichment of CD11c+ microglial gene signature in the spinal cord (149).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…mRNA-seq was performed as previously described (Elliott et al 2013). Briefly, total RNA was purified from the MEL cell cultures (miRNeasy; Qiagen).…”
Section: Mrna-seqmentioning
confidence: 99%